2017
DOI: 10.1111/jopy.12356
|View full text |Cite
|
Sign up to set email alerts
|

The life story from age 26 to 32: Rank‐order stability and mean‐level change

Abstract: These longitudinal results suggested that adopting new social roles, in this case becoming a parent, predicted how the life story was expressed, just as they seemed to influence other levels of personality, such as traits, following the social investment principle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
(149 reference statements)
4
18
0
Order By: Relevance
“…To address this issue, narrative researchers have started to systematically study consistency, stability, and change in personal narratives in several ways: by examining (a) the selection or deselection of events/details included in repeated tellings of narratives (Bauer, Tasdemir-Ozdes, & Larkina, 2014;K€ ober & Habermas, 2017;Mackinnon, De Pasquale, & Pratt, 2016;McAdams et al, 2006;Strauman, 1996;Thorne, Cutting, & Skaw, 1998), (b) how the meaning or interpretation of events may change (Josselson, 2009), (c) the choice of central themes in the narrative (Dunlop, Guo, & McAdams, 2016;McAdams et al, 2006), and (d) the structure/organization of the narratives as an index of an individual's narrative style (McLean, Pasupathi, Greenhoot, & Fivush, 2017). While prior studies have shown somewhat modest stability in regard to selection of events (Bauer et al, 2014;K€ ober & Habermas, 2017;Mackinnon et al, 2016;McAdams et al, 2006;Strauman, 1996;Thorne et al, 1998), the meaning/interpretation of events (Josselson, 2000) and narrative themes (Dunlop et al, 2016;McAdams et al, 2006;Sengsavang, Pratt, Alisat, & Sadler, 2017) have shown relatively more stability. However, the consistency and stability of narrative organization, as indexed by narrative coherence, are largely unknown.…”
Section: Personality and Narrativementioning
confidence: 99%
“…To address this issue, narrative researchers have started to systematically study consistency, stability, and change in personal narratives in several ways: by examining (a) the selection or deselection of events/details included in repeated tellings of narratives (Bauer, Tasdemir-Ozdes, & Larkina, 2014;K€ ober & Habermas, 2017;Mackinnon, De Pasquale, & Pratt, 2016;McAdams et al, 2006;Strauman, 1996;Thorne, Cutting, & Skaw, 1998), (b) how the meaning or interpretation of events may change (Josselson, 2009), (c) the choice of central themes in the narrative (Dunlop, Guo, & McAdams, 2016;McAdams et al, 2006), and (d) the structure/organization of the narratives as an index of an individual's narrative style (McLean, Pasupathi, Greenhoot, & Fivush, 2017). While prior studies have shown somewhat modest stability in regard to selection of events (Bauer et al, 2014;K€ ober & Habermas, 2017;Mackinnon et al, 2016;McAdams et al, 2006;Strauman, 1996;Thorne et al, 1998), the meaning/interpretation of events (Josselson, 2000) and narrative themes (Dunlop et al, 2016;McAdams et al, 2006;Sengsavang, Pratt, Alisat, & Sadler, 2017) have shown relatively more stability. However, the consistency and stability of narrative organization, as indexed by narrative coherence, are largely unknown.…”
Section: Personality and Narrativementioning
confidence: 99%
“…First, we assessed life story interviews at a single measurement occasion and were, thus, not able to test the stability or change of life narratives. Given that people continue to develop on each personality level over time (Roberts et al., 2006; Roberts & DelVecchio, 2000; Sengsavang, Pratt, Alisat, & Sadler, 2017), a fine-grained longitudinal perspective on personality in general and life narratives in particular would be promising to further understand the actor, agent, and author over time. More specifically, assessing features of the actor, agent, and author at multiple measurement occasions would allow for testing intraindividual change-change effects, that is, the extent to which changes in one personality level, such as personality traits, correspond to changes in another personality level, such as life goals or life narratives (Allemand & Martin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The authors further note that cognitive complexity was the most stable metric of participants’ personal narratives—more stable than emotional tone, agency, communion, personal growth, and number of words per sentence. In the study by Sengsavang et al (2017), individual differences in cognitive complexity (again, operationalized as integrative complexity and scored following guidelines updated by Baker-Brown et al, 1992) at 26 years of age were significantly correlated with those 6 years later at 32 years of age r (70) = .24, p < .05, further suggesting that there is trait component of cognitive complexity.…”
Section: Criteria Set 1: Generalizability and Stability Of Cognitive mentioning
confidence: 96%
“…Additional research conducted by McAdams et al (2006) and Sengsavang et al (2017) investigated various metrics, including cognitive complexity (operationalized as integrative complexity and scored following guidelines updated by Baker-Brown et al, 1992) of personal narratives provided by individuals during interviews over 3 and 6 years, respectively. In both of these studies, the rank-order stability of cognitive complexity (i.e., the stability of individual differences in cognitive complexity over time) was measured.…”
Section: Criteria Set 1: Generalizability and Stability Of Cognitive mentioning
confidence: 99%